Handbook of solvents. Volume 1, (ChemTec Publishing, 2014)
Each chapter in this volume is focused on a specific set of solvent properties which determine its choice, effect on properties of solutes and solutions, properties of different groups of solvents and the summary of their applications' effect. This includes effects on health and environment (given in tabulated form), swelling of solids in solvents, solvent diffusion and drying processes, nature of interaction of solvent and solute in solutions, acid-base interactions, effect of solvents on spectral and other electronic properties of solutions, effect of solvents on rheology of solution, aggregation of solutes, permeability, molecular structure, crystallinity, configuration, and conformation of dissolved high molecular weight compounds, methods of application of solvent mixtures to enhance the range of their applicability, and effect of solvents on chemical reactions and reactivity of dissolved substances.